Menanamkan Nilai-Nilai Moderasi Beragama di Lingkungan Sekolah : Upaya Meminimalisir Bullying - Muhammad Ashsubli (Reflection : Islamic Education Journal, 2025)
The phenomenon of bullying in schools remains a serious issue that affects students' psychological and social development. One strategic approach to minimizing bullying is by instilling the values of religious moderation within the school environment. Religious moderation promotes tolerance, justice, balance, and respect for diversity—principles that are essential in shaping students' character to live harmoniously in a plural society. This study aims to examine the role of religious moderation education in reducing bullying behavior in schools. A qualitative descriptive method was used, involving observation, interviews, and documentation in several secondary schools. The findings reveal that integrating the values of religious moderation into learning activities, school culture, and teacher role modeling contributes to creating an inclusive and welcoming school climate. Moreover, students become more aware of the importance of mutual respect and rejecting any form of violence. Therefore, embedding religious moderation values holds potential as a preventive solution to build a safe and supportive school environment for all members of the school community.